2018
DOI: 10.1088/1612-202x/aae220
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber single-longitudinal-mode narrow linewidth fiber ring laser with cylindrical vector beam output

Abstract: A single-longitudinal-mode (SLM) fiber ring laser with cylindrical vector beam (CVB) output is experimentally demonstrated. Mode selection and spectrum filtering are achieved by introducing a two-mode fiber Bragg grating (TM-FBG) as an output mirror simultaneously. The SLM operation is obtained by using a compound ring cavity laser structure together with an un-pumped EDF acting as a saturable absorber. The fiber laser operates at a single wavelength of 1545.99 nm with a 20 dB linewidth of about 7.1 kHz and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…8(a)] at peak 1, the fundamental mode was reflected back and the desired high-order mode was exported from the TMFBG. 111 Based on the offset-spliced fiber and TMFBG, Sun et al constructed the figure-8 fiber laser, 108 linear-cavity fiber laser, 106,112,113 and ring fiber laser 109,114 to directly generate RPB and APB. In the temporal domain, these cylindrical vector fiber lasers were capable of delivering continuous waves, microsecond pulses, nanosecond pulses, and picosecond pulses.…”
Section: Offset-spliced Fiber and Tapered Fiber For Generating Cvbsmentioning
confidence: 99%
“…8(a)] at peak 1, the fundamental mode was reflected back and the desired high-order mode was exported from the TMFBG. 111 Based on the offset-spliced fiber and TMFBG, Sun et al constructed the figure-8 fiber laser, 108 linear-cavity fiber laser, 106,112,113 and ring fiber laser 109,114 to directly generate RPB and APB. In the temporal domain, these cylindrical vector fiber lasers were capable of delivering continuous waves, microsecond pulses, nanosecond pulses, and picosecond pulses.…”
Section: Offset-spliced Fiber and Tapered Fiber For Generating Cvbsmentioning
confidence: 99%
“…It requires strong pump power and a long fiber length, which induces colossal loss. Jiang et al [16] demonstrated a switchable single longitudinal mode (SLM) narrow linewidth fiber laser with cylindrical vector beam (CVB) output. At 1543.35 nm and 1544.38 nm, the OSNR is higher than 60 dB, and the laser linewidth is 5.7 KHz and 6.8 khZ, respectively.…”
Section: Introductionmentioning
confidence: 99%